The human experience - DePoy, Elizabeth (Rowman & Littlefield, 2007)
And there was theory -- Explanatory legitimacy -- Scope of human description -- Explanations -- What is legitimacy? -- Longitudinal foundations -- Grand longitudinal approaches to describing and explaining human experience and behavior -- Specific longitudinal descriptions and explanations -- Environmental foundations -- Interior environment -- Exterior environment -- Categorical foundations -- Category membership on the basis of interior characteristics -- Category membership on the basis of exterior characteristics -- Systems descriptions and explanations -- Contemporary and emerging theories -- Longitudinal legitimacy -- Environmental legitimacy -- Categorical legitimacy -- Systems legitimacy -- Contemporary and emerging legitimacy -- Putting explanatory legitimacy to work.; Bibliographical references p. 267 - 280